Ex Officio Kepala Kantor Urusan Agama Kota Langsa Dalam Penyelesaian Wali Adhal - M. Affas Edward (Hukum Keluarga Islam IAIN LANGSA, 2020)
The people in Langsa City understand that when a wali adhal is considered more competent to solve it is the Office of Religious Affairs (KUA), because it is considered to have a better understanding of marriage issues. Whereas in regulations the juridical authority to resolve the problems of wali adhal is the religious court. The purpose of this research is based on the normative and sociological authority of the settlement of wali adhal. This research is field research with a sociological approach. The results show that there are several factors in the occurrence of wali adhal and the Office of Religious Affairs (KUA) is actively resolving wali adhal problems with mediation, emotional approach, discussion approaches and when the approach fails to be resolved by means of litigation.